Two seconds too late [large type] - Pettrey, Dani (Jeopardy Falls, 2025)
"In the stark but beautiful wilds of northern New Mexico, a luxury spa and couple's retreat turns into a chilling nightmare when a woman vanishes without a trace, just hours after a public fight with her boyfriend. Worried something sinister has happened, her friends reach out to investigator Riley MacLeod, an expert skip tracer, for help. The assignment means Riley must go undercover at the retreat, which means pairing up with private investigator Greyson Chadwick. Their partnership ignites a tumultuous mix of attraction and distrust as Riley's unorthodox methods clash with Greyson's meticulous approach. As they delve deeper into the case and a ruthless hitman is unleashed upon them, Riley and Greyson find themselves fighting not only for justice but for their very survival. Staying one step ahead of danger, the pair discovers a hidden truth that rocks them to the core. In their race against the clock, they can only hope that they're not too late."--